O discurso do líder ideal: modos de representação e identificação - Vilela, Juliana Souza (2020)
Leadership is a subject that permeates the social imagination as a source of desire, whether that of being a leader or having a leader who establishes order or accomplishes a great feat. In this sense, within the area of organizational studies and management, the leadership literature has endeavored to describe the profile of the ideal leader, selling the idea that organizations will be successful as they attract or develop extraordinary leaders. Understanding this movement as a kind of idealization of the leader, we start from a critique of the effects of this process in the organizational context, especially regarding the instrumentalization of this idea in stimulating pathological behavior patterns, in which they reinforce a perverse competition and sweeten the subject so that it does not notice certain contradictions in the world of work. In this sense, compulsive consumption by literature that conditions the subject to become an ideal leader is pernicious in that it induces him to work obsessively in a contradictory and fanciful behavior pattern, supported by the illusion that through his effort and investment in he will get a promotion. In order to analyze how the imperative of the ideal leader in the organizational context, considering the mainstream publications on leadership presented in the chapter of the theoretical framework, endorse an intention to define an ideal leader profile as an articulator of social relations in the organization, the present This thesis adopted Norman Fairclough's critical discourse analysis (CDA) as the method-theory of analysis of this discourse and certain Freudo-Lacanian psychoanalytic concepts such as idealization and identification. To this end, nine managers from the Human Resources area of large Brazilian companies were interviewed, who are responsible for hiring, developing, and allocating people to leadership positions. The interdiscursivity, the meaning of words, and evaluation were used as analytical-linguistic categories to explain the meanings that appear in the modes of representation and identification in the manager's discourse concerning the profile of the ideal leader. The managers identified themselves with personalities and ex-bosses who established a new order during their performance. Parental figures also influenced the identification of managers with the profile of an ideal leader. On the one hand, the fathers as a reference of 'law' and on the other, mothers as strong and welcoming women. As a result, it was identified that the discursive content of the adaptation and flexibility of the leader - which is present in the approach called "situational leadership" - was the most cited representation by managers as the speech that best defines the ideal leader for organizations. We also identified other discursive content, such as extraordinary ethical and relational standards, such as those prescribed in the so-called "authentic leadership," such as transparency, assertive communication, self-awareness, and the development of the leadership attitude in followers. However, such standards are conditioned by the principle of organizational results, since the ideal leader for HR managers is the subject that generates results through the team's performance. Finally, the speech of the ideal leader demonstrates that the logic of leadership takes the social imaginary as domination, which excludes the subject from the role of leader and transforms him into a disciplinarian who follows the instruments established by the business and management models.